Axitinib plus avelumab in the treatment of recurrent glioblastoma: a stratified, open-label, single-center phase 2 clinical trial (GliAvAx). Issue 2 (16th October 2020) - Awada, Gil; Ben Salama, Laila; De Cremer, Jennifer; Schwarze, Julia Katharina; Fischbuch, Lydia; Seynaeve, Laura; Du Four, Stephanie; Vanbinst, Anne-Marie; Michotte, Alex; Everaert, Hendrik; Rogiers, Anne; Theuns, Peter; et al.
Abstract : Background: No treatment demonstrated to improve survival in patients with recurrent glioblastoma (rGB) in a randomized trial. Combining axitinib with the programmed cell death ligand 1 blocking monoclonal antibody avelumab may result in synergistic activity against rGB. Methods: Adult patients with rGB following prior surgery, radiation therapy and temozolomide chemotherapy were stratified according to their baseline use of corticosteroids. Patients with a daily dose of ≤8 mg of methylprednisolone (or equivalent) initiated treatment with axitinib (5 mg oral two times per day) plus avelumab (10 mg/kg intravenous every 2 weeks) (Cohort-1). Patients with a higher baseline corticosteroid dose initiated axitinib monotherapy; avelumab was added after 6 weeks of therapy if the corticosteroid dose could be tapered to ≤8 mg of methylprednisolone (Cohort-2). Progression-free survival at 6 months (6-m-PFS%), per immunotherapy response assessment for neuro-oncology criteria, served as the primary endpoint. Results: Between June 2017 and August 2018, 54 patients (27 per cohort) were enrolled and initiated study treatment (median age: 55 years; 63% male; 91% Eastern Cooperative Oncology Group Performance Status 0–1). Seventeen (63%) patients treated in Cohort-2 received at least one dose of avelumab. The 6-m-PFS% was 22.2% (95% CI 6.5% to 37.9%) and 18.5% (95% CI 3.8% to 33.2%) in Cohort-1 and Cohort-2, respectively; median overall survival was 26.6 weeks (95% CI 20.8 to 32.4) in Cohort-1 and 18.0 weeks (95% CI 12.5 to 23.5) in Cohort-2. The best objective response rate was 33.3% and 22.2% in Cohort-1 and Cohort-2, respectively, with a median duration of response of 17.9 and 19.0 weeks. The most frequent treatment-related adverse events were dysphonia (67%), lymphopenia (50%), arterial hypertension and diarrhea (both 48%). There were no grade 5 adverse events. Conclusion: The combination of avelumab plus axitinib has an acceptable toxicity profile but did not meet the prespecified threshold for activity justifying further investigation of this treatment in an unselected population of patients with rGB.